2008
DOI: 10.1111/j.1745-7254.2008.00819.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between oxidative stress and modifications of cholinergic and glutaminergic receptors in the pathogenesis of Alzheimer's disease1

Abstract: Alzheimer's disease (AD) is the most common neurodegenerative disorder, and its pathogenesis is likely to be associated with multiple etiologies and mechanisms in which oxidative stress and deficits of neurotransmitter receptors may play important roles. It has been indicated that a high level of free radicals can influence the expressions of nicotinic receptors (nAChRs), muscarinic receptors (mAChRs), and N-methyl-D-aspartate (NMDA) receptors, exhibiting disturbances of cellular membrane by lipid peroxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…Brain region-selective sensitivity to the toxins may be determined by specific neuronal populations. Both the dopaminergic neurons [30] and the cholinergic neurons are particularly sensitive to oxidative stress [31]. Thus brain regions primarily relying on cholinergic transmission, such as the hippocampus and inhibitory neurons of the substantia nigra may be especially affected by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Brain region-selective sensitivity to the toxins may be determined by specific neuronal populations. Both the dopaminergic neurons [30] and the cholinergic neurons are particularly sensitive to oxidative stress [31]. Thus brain regions primarily relying on cholinergic transmission, such as the hippocampus and inhibitory neurons of the substantia nigra may be especially affected by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in addition to inhibiting 5-LOX activation induced by the elevated intracellular Ca 2+ via NMDA receptor activation [13] , baicalin also inhibits 5-LOX activation via the ROS/p38 MAPK pathway. In addition, there is crosstalk between NMDA-induced excitotoxicity and oxidative stress [29,30] , and baicalin inhibits 5-LOX activation after NMDA receptor-mediated excitotoxicity [13] . Whether baicalin affects a common pathway of 5-LOX activation in both pathological processes requires further investigation.…”
Section: Wwwchinapharcom LI Ct Et Almentioning
confidence: 99%
“…Studies have demonstrated that oxidative imbalance is a manifestation of AD that even precedes Aβ deposition and NFTs formation, and plays a crucial role in neuronal degeneration [5,6] . Increased oxidative stress (OS) has been implicated in the aging process and is a result of the imbalance between the generation and clearance of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%